Geographic and Breed Distribution Patterns of an A/G Polymorphism resent in the Mx Gene Suggests Balanced Selection in Village Chickens - Ommeh, S.; Jin, L.N.; Eding, H.; Muchadeyi, F.C.; Sulandari, S.; Zein, M.S.A.; Danbaro, G.; Wani, C.E.; Zhao, S.G.; Nie, Q.H.; Zhang, X.Q.; Ndila, M.; et al. (International Journal of Poultry Science, 2009)
An A/G Single Nucleotide Polymorphism (SNP) at position 1,892 of the Mx gene coding sequence has been linked to susceptibility/resistance to avian viral infection in vitro. Using PCR-RFLP and sequencing methods, 1,946 samples from 109 populations from Asia, Africa and Europe; grouped as indigenous village, commercial, fancy chicken as well as wild junglefowl were genotyped for the polymorphism. Allele and genotype frequencies were calculated. Only the G allele was present in Ceylon junglefowl Gallus lafayetti. Using the wild red junglefowl G. gallus population as reference, we assessed if the A/G alleles and genotypes frequencies have been affected by the breeding history and the geographic dispersion of domestic chicken. Within group variation was high but overall there were no significant variation in distribution of alleles and genotypes frequencies between the red junglefowl and indigenous village chickens (p>0.1946), with the exception of the East Asian group (p<0.0001). However, allele and genotype frequencies were significantly different between the red junglefowl and the commercial or fancy groups (p<0.0001). A small but significant negative correlation (r = - 0.166, p<0.0003) was observed between allelic and geographic distance matrices amongst indigenous village chicken populations. Human selection and genetic drift are likely the main factors having shaped today’s observed allele and genotype frequencies in commercial and fancy breeds. In indigenous village chicken and red junglefowl, we propose that both A and G alleles have been maintained by natural selection for disease resistance through a balancing selection mechanism.